PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN TERHADAP KINERJA MANAJERIAL DENGAN KOMITMEN SEBAGAI VARIABEL MODERATING - Megasari, Ervita; Kurnia, Kurnia (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This research is meant to examine the influence of the involvement of the preparation of budgetary participation to the managerial performance on Cooperative Service and Micro, Small and Medium Enterprises of Surabaya. This research is also meant to examine whether the organizational commitment moderates the budgetary participation to the managerial performance. This research has been conducted by using questionnaire survey method that is issued to 60 respondents and only 56 questionnaires return. The result of the research describes that the preparation of budgetary participation has an influence to the managerial performance and it describes that the significance level 0.00 is smaller than Î± = 0.05. The regression coefficient value of budgetary participation variable is 0.223, a positive sign on the regression coefficient that describes the unidirectional correlation between budgetary participation and managerial performance. It can be concluded that budgetary participation has significant and positive influence to the managerial performance whereas the moderation influence of the organizational commitment to the correlation between the preparation of budgetary participation and managerial performance is not supported by the result of this research. It is assumed that though a budget manager of Cooperative Service and Micro, Small and Medium Enterprises has high organizational commitment but it is only because the organizational structure forces him to participate or it is just a task. Therefore, it can be concluded that the second hypothesis is denied. Keywords: The Preparation of Budgetary Participation, Managerial Performance, and the Organizational Commitment